Restoration of antenna performance in the vicinity of metallic cylinder in implantable scenario. Issue 12 (23rd July 2020) - Ghosh, Jeet; Mitra, Debasis
Abstract : In this study, the authors propose an innovative solution based on mantle cloaking method to restore the performance of an implantable antenna, which is degraded due to the scattering from an adjacent metallic body. In an implantable device, the metallic body is generally used as a house for electronic circuitry. Initially, they investigate the deteriorating effects of metallic body on the antenna input impedance and radiation characteristics. Finally, by covering the metallic body with the designed metasurface, most of the antenna parameters are successfully retrieved. The proposed model is fabricated and measured with the in vitro test by immersing the antenna inside a muscle emulating gel, as well as, inside the minced pork.